Getting to know the Awá Tikal Nationality in Ecuador, cultural and linguistic aspects - Obando Arroyo, José Miguel; Pozo Follarán, Nancy Cecilia; Narváez Vega, Franklin Fernando (SATHIRI, 2024)
Apart from Spanish, Kichwa and Shuar there are 12 indigenous languages spoken in Ecuador. This study had the objective to determine the degree of vitality of Awapit in the center “El Baboso” settled in the province of Carchi. Open conversations with members of the center, a socio linguistic questionnaire to the Awapit speakers of the center and a semi structured interview to the director of the local school were used as tools for data collection. To stablish the diagnostic, there were used the six factors identified and stated in the Language Vitality and Endangerement document published by UNESCO. The data revealed that a reduced number of members of the center speak Awapit. Migration to Spanish speaking communities in search of education, better living conditions and healthcare areamong the causes for the loss of the language. In adittion, the use of Awapit is restricted to interactionsthat take place among the family members of the the language speakers, whereas Spanish is spoken in social and sport events. In the meetings organized by the so called Confederación de Centros Awa del Ecuador Spanish and Awapit are spoken by the participants. Currently, the children who attend the local school are taking Awapit lessons. However, it is too early to assess the impact of this action in the process of revitalizing the language. It was concluded that in the Awa Center el Baboso Awapit is in critical endangerament, its use is restricted to a limited number of domains and the response to new forms of comunication and media is minimal. It is important to continue taking actions in favor of revitalizing the language, otherwise, it could extinct and with it the culture of the Awa. To this end,four actions are included as recommendations that, if implemented in the center, will contribute to the revitalization process of the Awapit language in the Awa el Baboso Center.
Keywords: Awapit; linguistic vitality; diagnostic; endangered